Selection of the best consultant project using analytic hierarchy process - Noratira, Mohd Zainon (2018)
Consultant selection is a complex problem involving qualitative and quantitative multi criteria. In this study, an AHP-based consultant selection model is applied to develop and assist decision making to resolve the consultant selection problem in choosing the most favourable consultant's criteria combination. The Analytic Hierarchy Process (AHP) is an established decision method used to synthesize judgements and select the best alternative. When the objectives and scopes of study are set, then the data collection are made through two methods which are through literature review and a questionnaire survey. Information obtained from the questionnaire is interpreted into a simpler form and analysed by using the Expert Choice software. These data calculated by using Pairwise comparison. It is considered to be adequately consistent if the corresponding consistency ratio (CR) is less than 0.1 (<10%). A value less than 0.1 is good, however, the threshold of 0.1 is considered as the rule of thumb. The results of the survey depicts that there are similarities and dissimilarities between perceptions of respondents with a different background.